Literature Review Related to Cultural Identity Challenges of ESL Learners in African Rural Contexts - Chikwaka-Mpezeni, Maudy Precious; Chigwedere, Yuleth (International Journal of Language and Literary Studies, 2025)
This systematic review examines the complex relationship between cultural identity and English as a Second Language (ESL) acquisition in African rural contexts. A comprehensive literature search strategy was conducted across multiple academic databases, from which 127 peer-reviewed studies published between 2010 and 2024 were identified. Through an analysis of relevant theoretical frameworks and a purposively selected sample of 49 empirical studies, this examination synthesizes current understanding of how rural African learners navigate cultural identity challenges while acquiring English proficiency. The review integrates psychosocial theories, sociocultural learning theory, social learning theory, and postcolonial perspectives to provide a multidimensional understanding of the intersections between identity and language. The findings reveal that rural African ESL learners face unique challenges, including cultural identity conflicts, community resistance, intergenerational tensions, and limited culturally responsive pedagogical resources. They suggest that successful ESL acquisition in rural African contexts necessitates culturally responsive approaches that validate local identities while promoting English proficiency development. This review contributes to the growing body of literature on culturally sustaining pedagogy and provides recommendations for educators, policymakers, and researchers working in African rural educational contexts. The implications extend beyond language learning to encompass broader questions of cultural preservation, educational equity, and sustainable development in rural African communities.